ARI updates 2010 in collaboration with Faculty of Accountancy - UiTM, Accounting Research Institute (Accounting Research Institute (ARI), 2010)
Prior to the year 2000, research activities at the Faculty of Accountancy were very much informal and individual-driven. Individual researchers would get together and apply for some research grants either from UiTM or from accounting professional bodies such as the Malaysian Institute of Accountants (MIA), the Association of Chartered and Certifi ed Accountants (ACCA), The Chartered Institute of Management Accountants (CIMA), The Malaysian Institute of Certifi ed Public Accountants (MICPA) or the Australian Certifi ed Practicing Accountants (CPA Australia). As the groups get larger, researchers formed a team-based Special Interest Groups (SIGs). The emphasis of each SIG then was to conduct at least three research projects and to produce five publications per year.